PEMBENTUKAN PROFIL DAN KARAKTER GURU DALAM MENGHADAPI TANTANGAN - Ida Saadiyah (Pendidikan Seni Pertunjukan Fakultas Keguruan dan Ilmu Pendidikan Universitas Sultan Ageng, 2023)
Within the scope of education, teachers are the main factor in educating the nation's children. Improving the quality of teachers must be carried out in the internalization of character building. This can only be done if the teacher as a student model can show a personality of good character. This article aims to explore how important it is to design teacher training to improve smart teacher personalities.Keywords: Teacher, Character